2007
DOI: 10.1074/jbc.m700733200
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Trapping in an Epithelial Sodium Channel Pore Mutant

Abstract: The putative selectivity filter of the epithelial sodium channel (ENaC) comprises a three-residue sequence G/SXS, but it remains uncertain whether the backbone atoms of this sequence or whether their side chains are lining the pore. It has been reported that the S589C mutation in the selectivity filter of ␣ENaC renders the channel sensitive to block by externally applied Cd 2؉ ; this was interpreted as evidence for Cd 2؉ coordination with the thiol group of the side chain of ␣589C, pointing toward the pore lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…,b; Takeda et al. ). As shown in the model presented in Figure of an archetype ENaC subunit, which is based upon the chicken ASIC1 crystal structure as solved by the Gouaux laboratory (Jasti et al.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…,b; Takeda et al. ). As shown in the model presented in Figure of an archetype ENaC subunit, which is based upon the chicken ASIC1 crystal structure as solved by the Gouaux laboratory (Jasti et al.…”
Section: Discussionmentioning
confidence: 98%
“…,b; Takeda et al. ). Homologous series (S445 in cASIC1) at this position are highly conserved across all Deg/ENaC subunits and are recognized to contribute critical structure to the selectivity filter of channels formed by these proteins.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Substitution of the C-terminal Ser residue of the conserved G/S-x-S motif in the lower part of the TM2 (Ser589 in a ENaC) with large residues reduced the high selectivity of ENaC for Na + ions considerably (Kellenberger et al, 1999a). The likely explanation for this observation is that the mutations of a ENaC-S589 22 Kellenberger and Schild enlarge the pore diameter, allowing large cations, such as K + or ammonium, to permeate the ENaC pore (Kellenberger et al, 2001;Takeda et al, 2007). These and related studies identified the ion selectivity filter as the narrowest part of the ENaC channel pore, allowing almost exclusively monovalent cations of the size of Na + to pass through the channel pore (Kellenberger et al, 1999b;Snyder et al, 1999;Sheng et al, 2000).…”
Section: Asic Andmentioning
confidence: 99%
“…Mammalian target of rapamycin complexes (mTORCs) were found to play important roles in chemotaxis of several cell models such as neutrophils (Charest et al, 2010; Liu et al, 2010) and Dictyostelium (Sasaki and Firtel, 2006; Takeda et al, 2007; Liu and Parent, 2011). mTORC1 is activated in PI3K-dependent manner and its inhibition by rapamycin depressed the SCF-mediated migration (Kim et al, 2008a,b).…”
Section: Mast Cell Chemoattractantsmentioning
confidence: 99%